Analisa Beban Pendingin Ruangan AC Ruang Auditorium Gedung Pusat Lantai 7 Universitas PGRI Semarang - Ramadhani Saputra, Ananta; Spuriyadi, Slamet; Farikhah, Irna (Jurnal Rekayasa Mesin, 2025)
The Auditorium Room on the 7th Floor of the Central Building at Universitas PGRI Semarang is frequently used for various academic and non-academic activities, making cooling load analysis essential to maintain room temperature and humidity comfort. This study aims to determine the cooling capacity required in the auditorium. The methods employed include direct data collection through measurements, such as the number of occupants, electronic equipment, and room dimensions. Cooling loads were calculated by considering sensible and latent loads; sensible loads were measured based on temperature and equipment quantity, while latent loads were calculated based on air humidity. This study identified the total cooling load for the Auditorium Room on the 7th floor of the Central Building at Universitas PGRI Semarang as 115,155.501 Btu/hr. This cooling load consists of 82,381.608 Btu/hr of sensible load and 32,773.893 Btu/hr of latent load. The cooling load includes various factors, such as: Internal loads from occupants, electronic equipment, and lighting. External loads from glass radiation, walls, floors, roofs, and ventilation. The analysis results indicate that the current AC capacity needs to be reassessed to ensure its capability to achieve ideal room temperature and humidity.